Gender and preferences for non-farm income diversification: A framed field experiment in Ghana - Kramer, Berber; Lambrecht, Isabel B. (2019)
Many rural development programs aim at improving women’s economic empowerment in agriculture, but as rural income continues to diversify, women may prefer investing in nonfarm activities. In a framed field experiment with 1,527 participants in Ghana, we elicit preferences among both men and women for investments in crop farming versus alternative income-generating activities. We analyze gender differences in preferences and whether these can be ascribed to differential access to physical and human capital, or to differences in socio-economic characteristics, skills, perceptions and norms. We find that many respondents prefer to invest in both farm and non-farm activities. Women prefer investing significantly more towards non-farm diversification than men, but the gender gap is much smaller than expected a priori. Differential access to physical and human capital does not appear to explain this gap. Rather, the gender gap is associated with gender stereotyping of perceived skills. We conclude that both men and women reveal a strong preference for a diversity of income-generating activities, which needs to be reflected in programs and policies aiming to improve women’s economic empowerment.